Design of an aluminum can pressing machine using a lead screw mechanism with a microcontroller-based monitoring system - Rizal Indrawan; Abdulloh Sami Alfaris; Agus Khumaidi; Dhika Aditya Purnomo; Fipka Bisono (Politeknik Negeri Lhokseumawe, 2024)
The beverage industry is experiencing significant growth; however, the handling and management of can waste, particularly aluminum can waste, still rely on manual processes, such as stepping on or striking the can with a tool to reduce its volume. Therefore, there is a need for innovation to design and create a small-scale can pressing machine. The development of this machine employs the Ulrich method, which encompasses the identification of machine requirements, concept selection, and design embodiment. Based on the results obtained using the Ulrich method, design concept 2 was selected. Subsequently, planning, calculations, and analyses were conducted to identify the core and supporting components necessary for constructing the machine. The next stage involved creating detailed drawings of the machine, followed by fabrication and testing. During testing, the can pressing machine demonstrated the ability to exert a maximum load of 20,110.5 N, with a torque of 220.990 Nm and a power output of 0.5 HP (356.95 watts). The PZEM-004T microcontroller was utilized to monitor the operational control of the electric motor. The machine successfully reduced the volume of cans by 56.5%, decreasing their initial height from 345 mm to 150 mm, and it is capable of processing 75 cans per minute.